Social functioning and psychological problems as perceived by institutionalized and non-institutionalized elderly = (3GdGOGA GGdGLJeGYj h GdeTGcd GdfaSjg ceG jOQcgG GdeSfjf Gdebjejf ai OGQ GdQYGjg hNGQLgG (B/ s - Walaa Hassan Ragab Arafat; Naglaa Mostafa; Sayeda Ahmed Abdellatif; Zeinab Abdelhalim (Cairo : Walaa Hassan Ragab Arafat, 2016)
Ageing is a universal phenomenon and natural biological process of the life cycle. As people enter old age, they begin to experience associated changes in their physical, mental & social health. Therefore, elderly people are vulnerable to physiological, mental and social crisis. The aim of this study is to assess social functioning and psychological problems as perceived by institutionalized and non-institutionalized elderly, utilizing a descriptive comparative research design. A sample of convenience of 180 elderly which will be divided into: 90 institutionalized elderly was recruited from Hedaya Barakat geriatric home in Eldokki district, Giza city, Egypt and 90 non- institutionalized elderly was recruited from Pension and Disbursement settings, Tura El {u2013}Esment & Tura El-Balad post offices district, Cairo district, Egypt. Socio-demographic sheet, social functioning & psychological problems for elderly tools: were used to achieve the purpose of this study. The findings revealed that; half of the studied institutionalized and non institutionalized elderly had moderate levels of social functioning. In addition, the studied institutionalized elderly had higher levels of anxiety, loneliness, and depression than non institutionalized elderly and it was major problems. The studied non institutionalized elderly had higher level of psychological problems than institutionalized elderly. The study concludes that, the current study revealed that, psychological problems among the studied elderly affects negatively on their social relations and social functioning. Recommendation: nursing by education programs should be held for psychiatric mental health nurses in order to help families develop a better understanding of elderly people health needs, establishing geriatric centers for dealing with special medical, social and psychological problems and establishing rehabilitation units for geriatric people who suffering from mental illness advised to be introduced.
Thesis (M.Sc.) - Cairo University - Faculty of Nursing - Department of Psychiatric Nursing
Issued also as CD
Keywords: Institutionalized; Pychological problems; Social functioning